O28 Effects of a 4-week balance training and cognitive loading program in subjects with chronic ankle instability. (17th September 2017) - Gonzales, JM; Thomas, AC; Burcal, CJ; Howden, R; Kolesar, JM; Glover, BJ; Hubbard-Turner, T
Abstract : Study Design: 4 week training intervention. Background: Previous research has suggested that both dynamic balance training and concurrent cognitive tasks can improve postural control in subjects with chronic ankle instability (CAI). However, combining a traditional balance-training program with cognitive loading has not yet been investigated. Case Description: Eight subjects, (2 males and 6 females height=163.03±11.32, weight=73.88±8.34, age=19.6±1.3, with CAI completed this study. Static balance measures on a force plate were taken pre and post intervention. Subjects were assigned randomly to the dual task group or the traditional balance-training group. The balance training protocol was one established by McKeon. Both groups completed the balance training, however, the dual-task group also performed various cognitive tasks (backwards counting by 3 s and 7 s, and random number generation). Each group meet 3 times a week for 4 weeks. Outcomes: There was a significant group by time interaction (p=0.006) for anterior-posterior (AP) mean time-to-boundary (TTB). Those in the dual task group saw significant improvement (p=0.001) in AP mean TTB from pre-test (4.57±1.40) to post-test (6.02±1.28) compared to those in the traditional balance training group (pre=4.53±0.58; post=4.78±0.80). There was also a significant group by time interaction (p=0.005) for AP standard deviation TTB. Those in the dual task group saw significant improvement (p=0.001) in AP standard deviation TTB from pre-test (3.18±0.88) to post-test (4.37±.80) compared to those in the traditional balance training group (pre=3.01±0.68; post=3.22±0.82. Discussion: Preliminary data suggests those in the dual task group had significantly more improvements in AP mean TTB. With the inclusion of more subjects, it will be interesting to see if this difference continues in ML mean TTB. Dual task training may be a tool to add to rehabilitation plans to help further improve postural control.